THE CHARTS ANALYSIS OF METALLIC MATERIALS CYCLIC LOADING - Vakulenko, I. O. (Science and Transport Progress, 2009)
The questions of estimation of change character of relationship between amplitude and number of loading cycles up to fracture of specimens of carbon steel are considered.